Functional Plant-Based Beverage Fortified with Hazelnut Cuticle Polyphenols: Antioxidant and Phenolic Content Characterization - Raffaele Conte; Fabrizia Sepe; Sabrina Margarucci; Ezia Costanzo; Orsolina Petillo; Gianfranco Peluso; Loredana Marcolongo; Anna Calarco (Molecules)
In recent decades, there has been growing interest in the fortification of food products with antioxidants and phenolics derived from plant by-products. The present study focused on the production of a plant-based beverage enriched with hazelnut cuticle extract to characterize its antioxidant content, phenolic profile, and organoleptic characteristics. Liquid chromatography-mass spectrometry (LC-MS) enabled the identification of key polyphenols in hazelnut cuticles, including catechin, epicatechin, and quercetin derivatives, guiding the selection of a biocompatible Natural Deep Eutectic Solvent (NADES) composed of choline chloride and lactic acid for efficient extraction. The obtained phytochemical profile of the extract revealed a high concentration of bioactive compounds, with a Total Phenolic Content of 160.88 ± 14.27 mg GAE/g and Antioxidant Power measured by DPPH of 5848.2 ± 11.3 μmol TE/g. The bioaccessibility of phenolics in the fortified hazelnut-based beverage was determined after in vitro digestion, reaching a value of 89.7%, indicating excellent release and stability during digestion. Organoleptic evaluation revealed high sensory acceptability, with aftertaste scoring 3.61 ± 0.4 respect the 3.94 ± 1.3 result of reference milk, on a 5-point scale. In conclusion, this study demonstrates the potential for sustainable valorization of hazelnut cuticles, through their incorporation as NADES extracts in plant-based milk, providing an innovative solution to reduce food waste while catering to consumer demand for nutritionally enriched and eco-friendly products.